Magnetic transition temperatures follow crystallographic symmetry in samarium under high-pressures and low-temperatures. (21st December 2016) - Johnson, Craig R; Tsoi, Georgiy M; Vohra, Yogesh K
Abstract: Magnetic ordering temperatures in rare earth metal samarium ( Sm ) have been studied using an ultrasensitive electrical transport measurement technique in a designer diamond anvil cell to high-pressure up to 47 GPa and low-temperature to 10 K. The two magnetic transitions at 106 K and 14 K in the α-Sm phase, attributed to antiferromagnetic ordering on hexagonal and cubic layers respectively, collapse in to one magnetic transition near 10 GPa when Sm assumes a double hexagonal close packed ( dhcp ) phase. On further increase in pressure above 34 GPa, the magnetic transitions split again as Sm adopts a hexagonal- hP3 structure indicating different magnetic transition temperatures for different crystallographic sites. A model for magnetic ordering for the hexagonal- hP3 phase in samarium has been proposed based on the experimental data. The magnetic transition temperatures closely follow the crystallographic symmetry during α-Sm → dhcp → fcc / dist.fcc → hP3 structure sequence at high-pressures and low-temperatures.